Project Optimization of WEB-Based 3d Animation Bus Route Trans Jogja Using CPM - Retnowati, Nurcahyani Dewi (Institut Teknologi Dirgantara Adisutjipto, 2018)
The making of informative media in the form of three-dimensional animation on Trans Jogja bus routes really requires good project planning so that the process becomes more effective and efficient. In planning a project, it is necessary to consider the time, cost and scope of a project. Project optimization is done by using the Critical Path Method (CPM) method, which is a technique of analyzing network activity activities or project activities that predict total duration. Project optimization planning through the stages starting from the creation of the Work Breakdown Structure, barchart diagrams with Gantt Chart software, critical path calculations, and the final stages with CPM to determine the fastest time possible for the project to be completed. The results of the WBS are obtained by predecessor of each activity and its duration, the calculation of the critical path is 29 days with path a-b-c-d-e-f-g-h-I-j-l-m-n-o, and from the CPM calculation the total float is 0 so the project can be completed on time